Pain in Patients with Cancer Conditions - José Julio Ojeda González (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Pain is the most feared symptom in cancer patients. It manifests itself in 30 % of them at the time of diagnosis and between 70 and 80 % in the final stages of the disease. Pharmacological treatment, combined with non-pharmacological measures such as psychological and social care, contribute to controlling chronic pain in these patients in up to 95 % of cases. In the remaining 5 %, interventionist techniques must be used. The objective of this article is to make an update on the general elements and the treatment of pain in patients with cancer diseases. An updated review was carried out in the different databases on the subject. The best system for adequate pain control in patients with cancer conditions will be based on the analgesic ladder proposed by the World Health Organization.